CYBERSECURITY AND DATA PROTECTION IN THE MIDST OF THE ECONOMY 5.0 DIGITAL TRANSFORMATION - Gunawan Widjaja (Review of International Economy and Finance, 2025)
The digital transformation in the Economy 5.0 era brings significant challenges and opportunities in the fields of cybersecurity and data protection. The increased use of advanced technologies such as artificial intelligence, the Internet of Things (IoT), and big data complicates the threat landscape to data security, which encourages organisations to continuously update and adapt their security systems. On the other hand, these technologies also offer innovative solutions to strengthen data protection, such as more efficient threat detection through artificial intelligence and improved data transparency with blockchain technology. By combining technological innovation with strict security policies and global collaboration, organisations can effectively address cybersecurity challenges and ensure data protection in the rapidly evolving digital age.